Seroprevalensi Leptospirosis pada Anjing Kintamani di Bali - Mutawadiah, .; Puja, I Ketut; Sadra Dharmawan, Nyoman (Veterinary Science and Medicine Journal, 2015)
The aim of this study was to determine the seroprevalence of leptospirosis in Kintamani dogs in Bali. Bloodsamples were collected from 55 Kintamani dogs. The sera examination was conducted in the VeterinaryResearch Centre, Bogor. Microscopic Agglutination Test was performed to detect the presence ofantibodies against 14 leptospira antigens. The results showed that the prevalence of leptospirosis inKintamani dogs in Bali was 18.18% (10/55). Two out of 10 positive sera samples (3.64%) reacted withthree serovar; 5 (9.09%) reacted with two serovar; and 3 (3.64%) reacted with one serovar. There were fourtypes of serovars detected in this study, namely: Leptospira interrorgans serovar Celledoni, Leptospirainterrorgans serovar Canicola, Leptospira interrorgans serovar Cynopteri dan Leptospira interrorgansserovar Ichterohemorrhagiae. The research found that Leptospira interrorgans serovar Cellodini was verycommon in Kintamani dog.
Keywords: seroprevalence; leptospirosis; Kintamani dog; MAT